2016
DOI: 10.1007/s00223-016-0224-5
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines: A Possible Contribution to Vascular and Bone Remodeling in Idiopathic Pulmonary Arterial Hypertension

Abstract: Osteoporosis is a major comorbidity of cardio-respiratory diseases, but the mechanistic links between pulmonary arterial hypertension and bone remain elusive. The purpose of the stud was to evaluate serum adipokines and endothelin-1 (ET-1) levels in the patients with idiopathic pulmonary arterial hypertension (IPAH) NYHA class III-IV and to determine its associations with bone mineral density (BMD). Pulmonary and hemodynamic parameters, BMD Z-scores at the lumbar spine (LS) and femoral neck (FN), serum leptin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In the same context, a significant increase in adiponectin level was observed in patients with idiopathic pulmonary arterial hypertension (IPAH) than control subjects. Similarly, a significant correlation has been reported between serum adiponectin concentration and pulmonary vascular resistance [149], which was justified by the reflex increase in adiponectin level due to adiponectin resistance in this group of patients [150]. The same concept was proved by Domagała-Kulawik and colleagues who found that the median serum adiponectin levels were significantly reduced in obstructive sleep apnea patients compared to healthy subjects [151].…”
Section: • Pulmonary Hypertensionmentioning
confidence: 55%
See 1 more Smart Citation
“…In the same context, a significant increase in adiponectin level was observed in patients with idiopathic pulmonary arterial hypertension (IPAH) than control subjects. Similarly, a significant correlation has been reported between serum adiponectin concentration and pulmonary vascular resistance [149], which was justified by the reflex increase in adiponectin level due to adiponectin resistance in this group of patients [150]. The same concept was proved by Domagała-Kulawik and colleagues who found that the median serum adiponectin levels were significantly reduced in obstructive sleep apnea patients compared to healthy subjects [151].…”
Section: • Pulmonary Hypertensionmentioning
confidence: 55%
“…Adiponectin role is the attenuation of the excessive inflammatory response in the wall of the blood vessels of the placenta through inhibition of NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) signaling (it is a protein complex that controls transcription of deoxyribonucleic acid (DNA) and cytokine production), decreasing CRP (C-reactive protein) and increasing nitric oxide [42] via activating endothelial nitric oxide synthase and inhibition of superoxide in endothelial cells [43]. Besides, adiponectin mediated the process of trophoblast invasion by modulation of MMP/TIMP (matrix metalloproteinase to tissue inhibitor of metalloproteinase) balance (this is a ratio between active extracellular [11][12][13], hyperlipidemia [22], diabetic kidney disease [30], polycystic ovary [32], ovarian cancer, gestational diabetes [39], systemic sclerosis [74], breast cancer [98], lung cancer [99], colon cancer [100], thyroid cancer [106], prostate cancer [108,109], glioblastoma [113], AIS [129], Duchene Muscular Dystrophy [132], pulmonary hypertension [149], obstructive sleep apnea [151], atherosclerosis [11], hypertension [158], preeclampsia [41][42][43][44], COVID-19 [164] Cervical & endometrial cancer [37,38], joint inflammation [64], bone erosion in rheumatoid arthritis [65], SLE with renal involvement [87] Adipsin Systemic sclerosis with PAH [83], SLE with renal involvement [ Insulin resistance &diabetes [11,…”
Section: • Preeclampsiamentioning
confidence: 99%
“…Several studies have also reported an increase in adiponectin levels in PAH patients rather than a reduction confounding its role in PAH. 63,64 Insulin resistance is prevalent in PAH patients, and elevated levels of insulin have been shown to downregulate AdipoR1/R2 expression limiting adiponectin's physiological effect and resulting in adiponectin resistance. 65 Therefore, the increased circulating levels of adiponectin in PAH may be a result of the efforts of adipose tissues to prevent adiponectin functional resistance.…”
Section: Pah Adipokines and Obesitymentioning
confidence: 99%
“…Similarly in another study, adiponectin, leptin, and endothelin-1 levels in idiopathic pulmonary arterial hypertension (IPAH) patients’ serum were found to be higher than those in healthy volunteers. A significant correlation has been reported between serum adiponectin concentration and pulmonary vascular resistance (PVR) (r = 0.449, p = 0.009) [74]. Although serum adiponectin levels resulted increased in PH patients, within the endothelial cells, adiponectin was found to be reduced in patients with congenital heart disease with pulmonary hypertension (CHDPH).…”
Section: Adiponectin Prevents Pulmonary Hypertensionmentioning
confidence: 99%